How Biden can say goodbye to "America First" on nuclear issues. (2nd January 2021) - Mehta, Rupal
ABSTRACT: Efforts to renew international engagement with a deep bench of experts, intergovernmental organizations, and policy makers will be critical over the next four years to return to the core tenets of historical American foreign policy. There are three key areas where multilateral engagement will be needed with respect to nuclear policy: on Iran's nuclear program, on US alliances, and on the spread of nuclear technology to new countries.